(untitled) (Revista cientifica In Vestigium Ire, 2016)
This document aims to present a view from the comparison of the accounting and financial management of IAS 41 Agriculture IFRS for SMEs Section 34 Special activities and Decree 2649 of 1993; Thus from this comparison, their differences and similarities will be established in relevant aspects such as accounting treatment, scope, recognition, measurement and information to be disclosed. Seen that the accounting and financial treatment of these rules generate changes in the way it the registration of economic events was carried out, it will be expressed through application cases to provide guidance on the elements present. In that sense the results generated from the comparison show great significance in the measurement, which frame important differences in the restatement of financial statements.